Performa Reproduksi Induk dan Tahapan Perkembangan Larva Udang Vaname (Litopenaeus vannamei) - Supryady Supryady; Ardana Kurniaji; Ihwan Ihwan; Diana Putri Renitasari; Nursakinah Nursakinah (Jurnal Airaha, 2021)
The aim of this study to observe the reproductive performance and larval development of white shrimp broodstock with adequate feed and water quality control programs. The stages of research were preparation of cultivation media, selection of broodstock, spawning, hatching and rearing of larvae. The broodstock that were spawned came from Hawaii with a weight of 35 g/ind for the male broodstock and 40 g/ind for the female broodstock. The broodstock were fed with marine worms and squid. The larvae were given natural diet in the form of Artemia salina, Thallassiosira sp. and Skeletonema costatum and artificial feed. The results showed that the reproductive performance of the broodstock was observed with the number of eggs 102.400.000 eggs from 667 broods, the average fecundity per broodstock were 143.986 eggs, the number of naupli was 75.520.000 individuals, the hatching rate was 60.9%. Larval development starts from the egg stage which undergoes embryogenesis, hatches into naupli 1-6, then becomes zoea 1-3, mysis 1-3 and post-larvae (PL). Length growth from PL1-PL8 was 3.95-8.05 mm with a survival rate of 43.95%. Water quality during rearing is still in the optimum range for the growth of broodstock and shrimp larvae.